2001
DOI: 10.1086/319745
|View full text |Cite
|
Sign up to set email alerts
|

Avascular Necrosis of Bone in Patients with Human Immunodeficiency Virus Infection: Report of 6 Cases and Review of the Literature

Abstract: In 1998 and 1999, we diagnosed avascular necrosis of bone in 6 patients in our human immunodeficiency virus clinic practice, an incidence of 0.45%, which is 45 times greater than would be expected in the general population. Antiphospholipid antibodies and hyperlipidemia secondary to protease inhibitor therapy have been implicated as possible etiologies; however, these abnormalities cannot explain all cases of avascular necrosis of bone reported in patients with human immunodeficiency virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 11 publications
2
42
0
2
Order By: Relevance
“…12,13,51 However, several case-control studies have not found an association with antiret- roviral therapy; the most common risk factor has been previous treatment with systemic corticosteroids. 11,14,15,21 Similar to the adult studies, antiretroviral therapy was not an independent predictor of osteonecrosis in our study; the majority of cases and controls had been treated with antiretrovirals before the index case's LCPD diagnosis and 4 of the cases were diagnosed before the availability of PIs. Also similar to data in infected adults, 21,52 osteonecrosis was not associated with CD4 lymphocyte number, occurring in children with normal as well as low CD4 cell percentage.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…12,13,51 However, several case-control studies have not found an association with antiret- roviral therapy; the most common risk factor has been previous treatment with systemic corticosteroids. 11,14,15,21 Similar to the adult studies, antiretroviral therapy was not an independent predictor of osteonecrosis in our study; the majority of cases and controls had been treated with antiretrovirals before the index case's LCPD diagnosis and 4 of the cases were diagnosed before the availability of PIs. Also similar to data in infected adults, 21,52 osteonecrosis was not associated with CD4 lymphocyte number, occurring in children with normal as well as low CD4 cell percentage.…”
Section: Discussionsupporting
confidence: 83%
“…Bilateral disease was observed in 1 child; an increased frequency of multisite osteonecrosis has been described in HIVinfected adults. 11 Half of the HIV-infected children with LCPD were below the third percentile height at the time of diagnosis. Abnormal growth, as demonstrated by low birth weight and delayed bone age, is a reported risk factor for LCPD in the general pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a small series taken from a single infectious disease practice in the United States, the incidence of avascular necrosis in an HIV-positive population has been reported to be 45 times that seen in the general population (Brown & Crane, 2001). This could play a role in initial bacterial colonization.…”
Section: Osteomyelitis Secondary To Host Diseasementioning
confidence: 99%